"Comparaison n'est pas raison" (comparison is not reason enough) (XIIIth C French saying): A reply to Caspari. (September 2020) - Bourgeois, Jean; De Langhe, Kaatje; Ebel, Alexander V.; Dvornikov, Eduard P.; Konstantinov, Nikita; Gheyle, Wouter
Abstract: Reply to G. Caspari's remarks on our paper: "Geometric stone settings in the Yustyd Valley and its surroundings (Altai Mountains, Russia): Bronze Age 'virtual dwellings' and associated structures". Archaeological Research in Asia, 10, 17–31.